2018
DOI: 10.1002/jso.25078
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the adipokine genes ADIPOR1 and SPP1 is related to poor survival outcomes in colorectal cancer

Abstract: Upregulation of ADIPOR1 and SPP1, among the adipokine gene family, in cancer tissue is associated with poor survival in CRC, suggesting a potential mechanism linking obesity and CRC. ADIPOR1 and SPP1 expression could become useful prognostic indicators after further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…Sakellariou [13] and Gialamas [6] found that AdipoR1 is negatively associated with nodal stage and AdipoR2 is positively associated with TNM and shorter survival in lower stages of disease. In 2018, Chloe et al showed that increased tissue AdipoR1 messenger ribonucleic acid (mRNA) is associated with increased mortality and shorter OS [14]. Conversely, Ayyildiz et al [12] showed that tissue AdipoR1 and AdipoR2 have no influence on survival.…”
Section: Adiponectin (Apn)mentioning
confidence: 99%
“…Sakellariou [13] and Gialamas [6] found that AdipoR1 is negatively associated with nodal stage and AdipoR2 is positively associated with TNM and shorter survival in lower stages of disease. In 2018, Chloe et al showed that increased tissue AdipoR1 messenger ribonucleic acid (mRNA) is associated with increased mortality and shorter OS [14]. Conversely, Ayyildiz et al [12] showed that tissue AdipoR1 and AdipoR2 have no influence on survival.…”
Section: Adiponectin (Apn)mentioning
confidence: 99%
“…Similarly, SPP1 could not only promote CRC cell growth and migration, but it also inhibited autophagy, which may be thus achieved by activating the p38MAPK signaling pathway [29]. In addition, a study by Choe et al [30] also confirmed higher SPP1 expression along with shorter survival times in CRC patients.…”
Section: Discussionmentioning
confidence: 89%
“…Although prior studies have not addressed the association between the ADIPOR expression and prognosis in ovarian cancer, its upregulation was associated with poor survival in colorectal cancer. 41 The correlation between ADIPOR expression and tumor aggressiveness has also been demonstrated in esophageal and breast cancer. 42,43 Further studies are needed to clarify the predictive value of the ADIPOR in EOC and to identify therapeutic target against APN.…”
Section: Discussionmentioning
confidence: 96%